2017
DOI: 10.1101/177436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence-dependent nucleosome sliding in rotation-coupled and uncoupled modes revealed by molecular simulations

Abstract: While nucleosome positioning on eukaryotic genome play important roles for genetic regulation, molecular mechanisms of nucleosome positioning and sliding along DNA are not well understood. Here we investigated thermally-activated spontaneous nucleosome sliding mechanisms developing and applying a coarse-grained molecular simulation method that incorporates both long-range electrostatic and short-range hydrogen-bond interactions between histone octamer and DNA. The simulations revealed two distinct sliding mode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…We found significant differences between the dynamics of the 3 nucleosomes, the nucleosome with most TF binding sites showing the largest amplitude of breathing and twisting motions. This is in agreement with previous studies that revealed the more dynamic nature of natural nucleosomes 13,22,28 .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…We found significant differences between the dynamics of the 3 nucleosomes, the nucleosome with most TF binding sites showing the largest amplitude of breathing and twisting motions. This is in agreement with previous studies that revealed the more dynamic nature of natural nucleosomes 13,22,28 .…”
Section: Discussionsupporting
confidence: 94%
“…Despite the lack of full sampling convergence, we observed a good overlap between independent simulations for nucleosome breathing (Fig 3) and we achieved a wider conformational sampling by combining independent simulations of the same species into ensembles. This enabled us to study both breathing and twisting motions in the nucleosomes and to conclude about the sequence dependence of these motions at a level of detail not feasible in coarse grained simulations, which were previously used to study nucleosome dependent dynamics 22,28 . The atomic resolution provides the means to study the determinant modulators of nucleosome dynamics such the motion of histone tails or the role of anchoring histone residues 15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations